2015
DOI: 10.1007/s11240-015-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis of Pelargonium sidoides DC.

Abstract: Pelargonium sidoides is a high value medicinal plant endemic to South Africa and the Lesotho Highlands. Establishing an efficient regeneration system through somatic embryogenesis is necessary for its conservation. An efficient reproducible protocol for in vitro plant regeneration via somatic embryogenesis of Pelargonium sidoides, an important medicinal plant, is reported for the first time. Embryogenic callus was obtained on Murashige and Skoog (MS) basal medium supplemented with 2.0 mg L -1 picloram, 0.5 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In the study about Elaeis guineensis, the ability of NAA to promote somatic embryo development is poor compared with other PGRs [27]. Moreover, other PGRs, such as strigolactone and picloram, have been used to enhance SE in other plants [21,[36][37][38], and picloram performed better than NAA in Eucalyptus species [17]. However, in a study of Chamaecyparis thyoides L., SE was achieved without the help of plant growth regulators, and the authors speculated that PGRs have no effect on SE in some conifers including Chamaecyparis species due to their high endogenous indole-3-acetic acid (IAA) levels [22].…”
Section: Effect Of Plant Growth Regulators On Somatic Embryogenesismentioning
confidence: 99%
“…In the study about Elaeis guineensis, the ability of NAA to promote somatic embryo development is poor compared with other PGRs [27]. Moreover, other PGRs, such as strigolactone and picloram, have been used to enhance SE in other plants [21,[36][37][38], and picloram performed better than NAA in Eucalyptus species [17]. However, in a study of Chamaecyparis thyoides L., SE was achieved without the help of plant growth regulators, and the authors speculated that PGRs have no effect on SE in some conifers including Chamaecyparis species due to their high endogenous indole-3-acetic acid (IAA) levels [22].…”
Section: Effect Of Plant Growth Regulators On Somatic Embryogenesismentioning
confidence: 99%
“…This is in accordance with a report by Guo et al (2011), which stated that TDZ has auxin-and cytokinin-like effects in different plant species. Picloram, BAP, and 2,4-D were ineffective for shoot regeneration from calli in A. erectifolius; however, many studies have reported successful application of these growth regulators for enhancing shoot formation in strawberry (Kordestani and Karami, 2008), Urochloa species (Takamori et al, 2015), Vitis vinifera (Dai et al, 2015), Torenia fournieri (Chanchula et al, 2015), Pelargonium sidoides (Kumar et al, 2015), and Cordyline australis (Warchoła et al, 2015).…”
Section: Basementioning
confidence: 99%
“…plants were collected from the University of KwaZulu-Natal (UKZN) Botanical Gardens, Pietermaritzburg, South Africa. Sterilization was done as described by Kumar et al (2015). The leaf explants were excised into 10 mm sections and inoculated on MS (Murashige and Skoog, 1962) medium supplemented with 30 g L −1 sucrose, 0.1 g L −1 myo-inositol and different concentrations and combinations of picloram (0.5, 1.0, 2.0 M) and thidiazuron (TDZ) (1.0, 2.5, 5.0 M) for callus induction.…”
Section: Plant Callus Culturementioning
confidence: 99%